Radiographic comparisons of crestal bone levels around implants placed with low-speed drilling and standard drilling protocols: Preliminary results - Afsheen Tabassum (Elsevier, 2021)
Background: The present study aimed to investigate the mean crestal bone loss (CBL) by placing implants using two different drilling-protocols, i.e., standard drilling with saline irrigation and low-speed drilling without saline irrigation. Material and Methods: The patients were enrolled in the present study from a university teaching institute. Patients who fulfilled the inclusion criteria were randomly placed in two study groups: 1) control group: Standard drilling with saline irrigation and 2) test group: low-speed drilling without saline irrigation. The radiographic mean crestal bone loss (CBL) was evaluated at 3 months of follow-up before implant loading. Data analysis was performed using SPSS 20.0 (IBM product, Chicago, USA) and a p-value ≤ 0.05 was considered statistically significant. Results: Sixteen patients (10 males and 6 females) participated in the study. Thirty Camlog®-screw-line implants were placed (15 implants per study group). After 3 months of follow-up, the means CBL of implants placed with standard drilling and low-speed drilling protocols were 1.01 ± 0.49 mm and 0.74 ± 0.62 mm, respectively. No statistically significant difference could be recorded between two groups (p = 0.206). Conclusions: Dental implants placed with low-speed drilling without saline irrigation exhibited a similar CBL to implants installed with the standard drilling protocol. However, further randomised clinical trials are recommended to obtain stronger evidence and a better understanding of the effect of the low-speed drilling protocol without saline irrigation on mean CBL and long-term implant survival.